Environmental regulation: the welfare cost of BOD limitations in the palm oil industry - Abdul Rahim, Khalid (Penerbit Universiti Kebangsaan Malaysia, 1991)
The Malaysian palm oil industry is on the chief contributor to the nation's economy. Despite all the successes the palm oil industry has achieved in the international arena, domestic problems arising from the rapid development of the industry has had serious consequences on the natural environment. It has been singled out as the most polluting agro-based industry and thus, environmental regulation governing its effluent discharge in processing has been enforced. The impacts of this regulation on the welfare of the polluter, the consumer and the resource owner in terms of changes in economic surpluses are evaluated using a vertically integrated market model. Results support the hypotheses about the direction of the effects of this regulation, but these effects have been rather small for the crude palm oil producers who are directly regulated. The impacts are passed on to refiners and the suppliers of raw materials.